PERBANDINGAN ESTIMASI BIAYA STRUKTUR BANGUNAN ANTARA SOFTWARE AUTODESK REVIT DENGAN CUBICOST - Ayu Herzanita; Refina Putri Anggraini (Construction and Material Journal, 2023)
Building Information Modeling (BIM) software commonly used in Indonesia to calculate cost estimates includes Autodesk Revit and Cubicost. Previous studies have shown significant differences comparing the estimated cost of structural work in Autodesk Revit with conventional methods. Further study is needed to compare Autodesk Revit with Cubicost in the same project, with the purpose of knowing the difference in the estimated cost of structural work. The object of this study was the Urban Homes Residential Apartment construction project by reviewing the upper structure. The chosen research strategy was in accordance with the case study objectives. The process begins with the preparating of the WBS (Work Breakdown Structure), designing the BIM 3D, calculating the estimated structural work cost resulting from quantity takeoff using work unit price analysis, and analyzing the estimated cost comparison between Cubicost and Revit BIM software. Based on the analysis results, the estimated cost of building structures using Cubicost is Rp 80,485,995,692, - and has differences of ±13.1% compared to using Revit.